2013
DOI: 10.1111/jvh.12148
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of observational studies: hepatitis C and survival after renal transplant

Abstract: Recent evidence has shown that anti-HCV-positive serologic status is significantly linked to lower patient and graft survival after renal transplant, but conflicting results have been given on this point. The aim of this study was to conduct a systematic review of the published medical literature concerning the impact of HCV infection on all-cause mortality and graft loss after RT. The relative risk of all-cause mortality and graft loss was regarded as the most reliable outcome end-point. Study-specific relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 40 publications
1
96
1
Order By: Relevance
“…144,145 In CH-C patients with ESRD, altered drug pharmacokinetics, increased susceptibility to drug-related toxicity, the requirement for renal transplantation, and a modified course of disease make their treatment difficult. Some of the other issues, which are peculiar to this population of patients, include normal or minimal elevation of transaminases, GT-1 predominance, inaccurate noninvasive assessment of hepatic fibrosis especially with transient elastography, and higher complication rate after liver biopsy.…”
Section: Management Of Hcv In End-stage Renal Failure (Esrd) and Renamentioning
confidence: 99%
“…144,145 In CH-C patients with ESRD, altered drug pharmacokinetics, increased susceptibility to drug-related toxicity, the requirement for renal transplantation, and a modified course of disease make their treatment difficult. Some of the other issues, which are peculiar to this population of patients, include normal or minimal elevation of transaminases, GT-1 predominance, inaccurate noninvasive assessment of hepatic fibrosis especially with transient elastography, and higher complication rate after liver biopsy.…”
Section: Management Of Hcv In End-stage Renal Failure (Esrd) and Renamentioning
confidence: 99%
“…3,[11][12][13] However, a meta-analysis of observational studies in RTRs with HCV demonstrated increased all-cause mortality and all-cause graft loss in these patients. 14 In RTRs who become infected with HCV after transplant, the duration from receiving a transplant to acquiring the infection was an important predictor of survival. 15 In our study, 25 of 37 patients had developed HCV infection after renal transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses have shown that HCV+ kidney transplant recipients have a 79% higher risk of all-cause mortality versus HCVnegative kidney transplant recipients. 8,10 The only other study that used the national database in a manner similar to our study was by Batty and associates in 2001, which studied patients from 1994 to 1997 with a follow-up to 36 months. 17 Their results were similar to ours, and in fact our study extends their results up to the 13-year follow-up available.…”
Section: Discussionmentioning
confidence: 99%
“…As for graft survival, many previous studies demonstrated that HCV seropositive patients have lower patient and graft survival than seronegative patients after kidney transplant. 8,10 Most of these studies are from the prior decade with older immunosuppression strategies and single center.…”
Section: Introductionmentioning
confidence: 99%